Joyland - King, Stephen, 1947- (London : Hard Case Crime/Titan Books, 2013)
Set in a small-town North Carolina amusement park in 1973, Joyland tells the story of the summer in which college student Devin Jones comes to work as a carny and confronts the legacy of a vicious murder, the fate of a dying child, and the ways both will change his life forever.
Keywords: City and town life -- North Carolina -- Fiction; Amusement parks -- Fiction; Nineteen seventies -- Fiction; Carnivals -- Fiction; College students -- Fiction; Cold cases (Criminal investigation) -- Fiction; Murder -- Investigation -- Fiction; Life change events -- Fiction; North Carolina -- Fiction; Mystery fiction; Ghost stories